PENGARUH MAKROEKONOMI TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN - Amalia Nur Chasanah (STIE Pelita Nusantara Semarang, 2021)
The economic condition of a country will affect the investment climate in that country. This study aims to determine the effect of macroeconomic variables on stock returns in banking companies in Indonesia. The macro variables used are inflation, interest rates, exchange rates and Gross Domestic Product (GDP). The sample used in this research is banking companies listed on the IDX in 2013-2019 with a sample size of 84. The data analysis technique used is multiple regression with the classical assumptions of multicollinearity, autocorrelation, heteroscedasticity and normality. The results showed that the inflation variable, interest rate and exchange rate had a significant negative effect on stock returns. Meanwhile, the GDP variable does not have a significant negative effect on stock returns. The adjusted r square value is 0.137 which means that the variables of inflation, interest rates, exchange rates and GDP are able to explain stock returns of 13.7%, while the rest is explained by other variables not in this study.